Home Literacy Environment and Shared Reading in the Newborn Period. Issue 1 (January 2018) - Sinclair, Elizabeth M.; McCleery, Ellen J.; Koepsell, Lorraine; Zuckerman, Katharine E.; Stevenson, Ellen B.
ABSTRACT: N/A: In 2014, the American Academy of Pediatrics and Reach Out and Read formally emphasized counseling families on shared reading starting at birth. However, little data exist on the home reading practices and environments of newborn infants. Objective: To characterize the home reading practices and environments of 2-week-old infants. Methods: We distributed writtens self-administered surveys to 223 families seen for 2-week well-child visits. The survey assessed the frequency of shared reading, "favorite activities" with infants (including shared reading), number of books in the home, and sources of reading information. Descriptive and multivariate statistics were computed to assess the frequency of primary outcomes and sociodemographic associations. Results: At the 2-week well-child visit, 57.7% of families had not yet started reading with their infants. A minority of families (29.1%) reported shared reading as a favorite activity. Thirty-five percent of families reported having ⩽10 books in the home. Non-white race and having lived outside the United States were significantly associated with having ⩽10 books in the home. Parents who reported not always enjoying reading were less likely to have started reading to their infant. Conclusion: Differences in both book ownership and having initiated shared reading are present from the newborn period. Findings suggest an opportunity for the provision of children's books in early infancy through primary care, particularly for immigrant and minority families. Engaging parents to incorporate language-rich activities, including shared reading, with their infants may be especially important for those who have a history of not being read to or who do not report enjoying reading.